Capillary electrophoresis-MALDI interface based on inkjet technology - Vannatta, Michael W. (2009)
An ink jet printer valve and nozzle were used to deliver matrix and sample from an electrophoresis capillary onto a MALDI plate. The system was evaluated by separation of a set of standard peptides. That separation generated up to 40,000 theoretical plates in less than three minutes. Detection limits were 500 amol using an ABI TOF-TOF instrument and 2 fmol for an ABI Q-TOF instrument. Over 70% coverage was obtained for the tryptic digest of α-lactalbumin in less than 2.5 minutes.